Petroleum Resource Potential Assessment of Members 1 and 3 of the Paleogene Shahejie Formation, Qikou Sag: Insights from Hydrocarbon Generation and Expulsion Capabilities - Zhuoya Wu; Xianzheng Zhao (Energies, 2022)
The Shahejie Formation (Fm) in the Bohai Bay Basin is well-known for its substantial conventional resource potential and long-term history of exploration. Shale oil has been confirmed as a sustainable resource following breakthroughs in shale exploration in the first and third members of the Paleogene Shahejie Fm (Mbr1 and Mbr3) in Qikou Sag, particularly Mbr3, which has a more desirable output. However, the limited distribution of exploration wells for shale oil around the southwest of Qikou Sag calls for a comprehensive evaluation of shale oil (or gas) potential in all of Qikou Sag. Here, we clarify the shale oil (or gas) resource potential and areas favorable for exploration in Mbr3 by using a hydrocarbon generation potential model (HGPM) based on the material balance method and the principle of hydrocarbon (HC) generation dynamics. Apart from the quantified characteristics of the oil generation process of Mbr3 source rocks, the source rocks of both Mbr1 and Mbr3 were compared to interpret the discrepancies in HC generation. The results show that Mbr3 source rocks have high-quality geological and geochemical features, a thickness of 1200 m, and adequate organic matter (1.66% TOC on average, dominated by kerogen II&III, and in the mature stage). The threshold of expulsion is Ro = 0.78%; correspondingly, HC generation potential (Qg), HC expulsion potential (Qe), and retention potential (Qr) are, at maximum, 605.89, 169.65, and 436.24 mg HC/g TOC. The intensity of HC generation (Ig), expulsion (Ie), retention (Ir), and effective retention (Ire) is focused on the main depression and the Qibei Sub-sag and can reach as high as 250 × 104, 65 × 104, 170 × 104, and 110 × 104 t/km2, respectively. The resource potential for the retention of shale was calculated to be 13.3 × 108 t (movable shale oil and gas 8.0 × 108 t), and conventional and tight oil or gas resources were calculated to be 4.7 × 108 t (equivalent oil resources). Favorable exploration targets are spread around the main depression and the Qibei Sub-sag. There are disparities in the thermal process and thermal generation, and expulsion features between Mbr1 and Mbr3 source rocks are derived from kerogen-type and non-isolated deposit environments. Thus, a quantitative, advanced evaluation and a comparison offer more precise exploration predictions of shale in this Fm and further boost the low-risk exploration process.